Diet-related practices and BMI are associated with diet quality in older adults. Issue 7 (2nd July 2013) - Ford, Dara W; Hartman, Terryl J; Still, Christopher; Wood, Craig; Mitchell, Diane; Hsiao, Pao Ying; Bailey, Regan; Smiciklas-Wright, Helen; Coffman, Donna L; Jensen, Gordon L
Abstract Objective To assess the association of diet-related practices and BMI with diet quality in rural adults aged ≥74 years. Design Cross-sectional. Dietary quality was assessed by the twenty-five-item Dietary Screening Tool (DST). Diet-related practices were self-reported. Multivariate linear regression models were used to analyse associations of DST scores with BMI and diet-related practices after controlling for gender, age, education, smoking and self- v. proxy reporting. Setting Geisinger Rural Aging Study (GRAS) in Pennsylvania, USA. Subjects A total of 4009 (1722 males, 2287 females; mean age 81·5 years) participants aged ≥74 years. Results Individuals with BMI < 18·5 kg/m2 had a significantly lower DST score (mean 55·8, 95 % CI 52·9, 58·7) than those individuals with BMI = 18·5–24·9 kg/m2 (mean 60·7, 95 % CI 60·1, 61·5; P = 0·001). Older adults with higher, more favourable DST scores were significantly more likely to be food sufficient, report eating breakfast, have no chewing difficulties and report no decline in intake in the previous 6 months. Conclusions The DST may identify potential targets for improving diet quality in older adults including promotion of healthy BMI, breakfast consumption, improving dentition and identifying strategies to decrease concern about food sufficiency.